Simplify: -4b(5a – 2b ) + 4(-3ab – 5b^2)

Question

Asked 2/3/2012 5:42:06 PM

Updated 8/11/2014 10:02:02 PM

2 Answers/Comments

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

migzptz|Points 4871|

Question

Asked 2/3/2012 5:42:06 PM

Updated 8/11/2014 10:02:02 PM

2 Answers/Comments

Rating

5

The steps are as follows:

-4b(5a – 2b ) + 4(-3ab – 5b^2)

=-4b*5a-(-4b)*(-2b)+4*(-3ab)+4*(-5b^2)

=-20ab+4b*2b-12ab-20b^2

=-20ab+8b^2-12ab-20b^2

=-(20ab+12ab)+(8b^-20b^2)

=-32ab+(-12b^2)

=-32ab-12b^2.

-4b(5a – 2b ) + 4(-3ab – 5b^2)

=-4b*5a-(-4b)*(-2b)+4*(-3ab)+4*(-5b^2)

=-20ab+4b*2b-12ab-20b^2

=-20ab+8b^2-12ab-20b^2

=-(20ab+12ab)+(8b^-20b^2)

=-32ab+(-12b^2)

=-32ab-12b^2.

Added 8/11/2014 10:02:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [8/11/2014 11:44:15 PM]

solve for x: show steps 8x + 4 = 4x – 4 **Weegy:** 8x + 4 = 4x - 4
8x - 4x = - 4 - 4
4x = - 8
x = - 8/4
x = - 2 (More)

Question

Expert Answered

Updated 4/15/2014 1:50:22 PM

0 Answers/Comments

solve for x with steps 4x – 4 + 3x = 3x + 5 – 5x **Weegy:** 4x+3x-4=3x-5x+5
7x-4=-2x+5
7x+2x=5+4
9x=9
x=9/9
x=1
(More)

Question

Expert Answered

Updated 1/14/2018 4:01:28 PM

0 Answers/Comments

solve for x with steps 4( x – 2 ) = 5( x + 3) **Weegy:** 9x (More)

Question

Expert Answered

Updated 4/15/2014 1:49:31 PM

2 Answers/Comments

4( x – 2 ) = 5( x + 3);

4x-8 = 5x+15;

4x - 5x = 15 + 8;

-x = 23;

x = -23

4x-8 = 5x+15;

4x - 5x = 15 + 8;

-x = 23;

x = -23

Added 4/15/2014 1:49:31 PM

This answer has been confirmed as correct and helpful.

solve for x (show steps) 4( x – 2 ) = 5( x + 3)

Question

Not Answered

Updated 3/26/2018 3:45:04 AM

1 Answer/Comment

4( x - 2 ) = 5( x + 3)

(4)(x)+(4)( - 2)=(5)(x)+(5)(3)

4x - 8 = 5x + 15

4x - 8 = 15 - 5x

- x - 8 = 15

- x = 15 + 8

- x = 23

x = 23/-1

x = - 23

(4)(x)+(4)( - 2)=(5)(x)+(5)(3)

4x - 8 = 5x + 15

4x - 8 = 15 - 5x

- x - 8 = 15

- x = 15 + 8

- x = 23

x = 23/-1

x = - 23

Added 3/26/2018 3:45:00 AM

This answer has been confirmed as correct and helpful.

solve for x (show steps)4( x – 2 ) = 5( x + 3) **Weegy:**
4( x – 2 ) = 5( x + 3);
4x - 8 = 5x + 15;
4x - 5x = 15 + 8;
-x = 23;
x = -23
(More)

Question

Expert Answered

Updated 7/28/2014 1:05:54 PM

0 Answers/Comments

39,052,759

questions answered

There are no comments.